0D polymer nanocomposite carbon-paste electrodes using carbon nanohorns: Percolating networks, electrochemical achievements and filler comparison. (8th September 2020) - Montes, R.; Baeza, M.; Muñoz, J.
Abstract: In this preliminary work, carbon nanohorns (CNHs) have been dispersed for the first time in an inert polymeric matrix for the development of a new 0D CNH-based polymer nanocomposite carbon-paste electrode (pNC–CPE). As a first demonstration, the electrically conductive networks were optimized by tuning the filler/polymer composition ratio in order to achieve transducers with enhanced electroanalytical responses. Further, direct electrochemical comparison with additional pNC–CPEs employing conventional carbon nanoallotropes is provided, demonstrating that pNC–CPEs can be electrically modulated by customizing the filler/polymer composition ratio as well as the carbon nature. Consequently, this work wide the pNC–CPE family and paves the way for exploiting CNH-based polymer nanocomposites as novel sensitive and reproducible electrochemical (bio)sensing devices.